Short imidazolium chains effectively clear fungal biofilm in keratitis treatment - Liu, Lihong; Wu, H.; Riduan, S.; Ying, J.; Zhang, Y. (2013)
Fungal keratitis is a leading cause of ocular morbidity throughout the world. However, current therapies against fungal keratitis are often ineffective. Herein, we have developed the amphiphilic main-chain imidazolium polymer (PIM-45) and oligomer (IBN-1) materials that can efficiently inhibit the growth of fungi with low minimal inhibition concentration (MIC) values and clear the fungal biofilm, while displaying minimal hemolysis. In vivo keratitis treatment indicates that topical solutions of these polyimidazolium salts (PIMSs) are safe and as effective as that of amphotericin B, the most commonly used agent for the treatment of Candida albicans (C. albicans) keratitis. Compared to the costly and unstable amphotericin B and fluconazole, PIM-45 and IBN-1 are easy to prepare, inexpensive and stable. They can be stored in phosphate-buffered saline (PBS) solutions with long shelf life for routine topical use.